Desain Teknologi Penyaringan Air Menggunakan Pasir Kerubung - Riski Muliyani; Yudi Kurniawan; Iip Istirahayu (STKIP Singkawang, 2020)
The purpose of service programs was designed for water filter by using kerubung sand. The method of designing the water purification was literature study on the specifics articles that related to the simple water purification process with the slow water filter method. The development of the filter method by the service team using the kerubung sand. The service teams’ considerations in choosing local materials as the main component as water purification because it was easy to get, less price event some things can be obtained for free because they were available in the wild, or it can be made easily. The results of the water purification design by using the slow water method with kerubung sand had been proportion of 15: 4: 4: 1 with the types of materials were kerubung sand, zeolite sand, the palm fiber, and activated carbon, respectively. It is hoped that the successful creation of the water purification design composition of the slow water method using kerubung sand will make the quality of water produced from the filter process better than before. The addition output of this service program was the publication of copyright certificate of the manual book for slow water purification method. The conclusion that can be concluded from this design process was that the use of kerubung sand as a filter media is alleged to be a solution for filtering well water at the location of PKM partners